Qur'anic Ecotheology as Environmental Critique: Reinterpreting Fasad fi al-Ard in QS. Ar-Rum [30]: 41 in Extractive Economic Practices - Helmi, Fahmi; Nurhakim, Ilham; Munawar, Asep (QiST: Journal of Quran and Tafseer Studies, 2026)
This research aims to analyze the concept of fasād fī al-arḍ and examine its empirical implications for environmental degradation caused by sand mining in Kampung Bungbang, West Java. Unlike previous ecotheological studies that focus predominantly on textual-normative discourse, this study offers a distinct analytical framework by operationalizing the concept of fasād as a diagnostic indicator for specific ecological crises. A qualitative method was employed, integrating tafsir maudhu'i (thematic interpretation) with field research involving 12 key informants and direct observations conducted in December 2025. The findings demonstrate that sand mining activities in the area constitute a tangible form of fasād fī al-arḍ, manifesting in infrastructure deterioration, land degradation, and heightened landslide risks. Furthermore, the social dimension is significantly impacted, particularly concerning the health and psychological comfort of residents. This study concludes that environmental revitalization must transcend technical solutions to include a paradigm shift centered on the principles of khilāfah (managerial responssibility) and mīzān (ecological balance). The novelty of this work lies in its integration of theological values with empirical-contextual evidence, providing a benchmark for sustainable policy-making to prevent the legitimization of ecological disasters.